2015
DOI: 10.5588/ijtld.14.0772
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis is frequently diagnosed within 12 months of diabetes mellitus

Abstract: The risk of developing TB was increased among DM patients, particularly during the first 12 months after DM diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…Patients who took anti‐diabetic drugs at least once or with ICD‐10 codes for DM (E11‐E14) at least once between 1 January 2007 and 31 December 2008 were excluded. To identify new cases of TB, we excluded patients who took either anti‐TB drugs or with ICD‐10 codes for TB (A15‐A19, U88‐U88.1) before the diagnosis of DM . We excluded patients if the regions in which they were initially diagnosed with DM and TB were different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who took anti‐diabetic drugs at least once or with ICD‐10 codes for DM (E11‐E14) at least once between 1 January 2007 and 31 December 2008 were excluded. To identify new cases of TB, we excluded patients who took either anti‐TB drugs or with ICD‐10 codes for TB (A15‐A19, U88‐U88.1) before the diagnosis of DM . We excluded patients if the regions in which they were initially diagnosed with DM and TB were different.…”
Section: Methodsmentioning
confidence: 99%
“…However, to date, there has been no study investigating whether such risk factors are actually associated with the regional differences in the TB burden. In the present study, we applied a previously reported cohort of patients with newly diagnosed diabetes mellitus (DM), which is another important risk factor for the development of TB, as a means to analyse the relationship between several risk factors and regional differences in TB incidence.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting finding is that 7% of the people with DM reported prior TB history, and over 50% of prior TB was diagnosed before a DM diagnosis. Of these, 11% reported previous TB diagnosis within the first 2 years of DM diagnosis [22]. Screening for TB among people with DM is now strongly recommended in India [6, 23], though there is a need to identify specific factors among people with DM that increase risk of TB so that screening can be targeted and effective.…”
Section: Discussionmentioning
confidence: 99%
“…2 As a matter of fact, the same group had previously observed that the incidence of TB infection occurred most frequently within the first year from DM diagnosis. 3 On the contrary, Lee et al had shown that the prevalence of diabetes was higher in patients with pulmonary tuberculosis compared to the general population. 4 Since this subject is of wide interest and continuously evolving, we would like to highlight some aspects.…”
Section: Dear Editormentioning
confidence: 96%